Design a Density Map of Chinese Tourists Journey in Chiang Mai City - Wang Bo (2020)
© 2020 IEEE. Chiang Mai, as the second largest city of Thailand, attracts a large number of tourists to come. Chinese tourists, which are the main tourist group, are very important for Chiang Mai tourism industry. To help the Chiang Mai Tourism Administration to better improve tourism facilities, a tourist density map which shows the density of tourists in different time periods and different places is required. The objective of this study is to design a tourist density map of Chinese tourists. Data collection of this research is from a Chinese tourism website called Mafengwo, by using text mining as the main tool to capture Chinese tourist's comments under tourist behavior theory. Based on behavior analysis, then a tourist density map is designed to understand the differences in the density distribution of Chinese tourists in various attractions. This article is divided into four parts, firstly is the introduction part with research background and problem identification, and second part gives an over view of theories and methods to conduct the research: Then research methodologies is delivered in details in third part; and last part is research result and conclusion.